The Effectiveness of AI Speech Recognition on Students’ English Pronunciation - Woro Kusmaryani; Ramli; Winarno (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background:  Pronunciation is probably one of the most problematic and the conventional teaching approaches do not tend to offer the immediate, personal feedback, which is required to achieve effective pronunciation. But AI speech recognition applications can provide a real-time corrective response that may be used to overcome these drawbacks in teaching. Methodology:  The research utilized a pre experimental one group pre-test post-test study design whose qualitative observations were supported by 30 first-semester students purposely selected to participate in the study. The information was gathered by means of pre- and post-teaching tests, observation forms, and AI-based feedback. The quantitative analysis was based on descriptive statistics and paired sample t-test, and instead, thematic coding based on observation was applied to qualitative data. Findings:  The results showed that the pronunciation of students has been significantly improved, and the average scores have increased by 68.4 to 81.7 (p < 0.05). The qualitative observations revealed the enhancement of the accuracy in the production of segmental characteristics, including the interdental sounds (/θ/, /ð/), voicing contrasts (/v/ vs. /f/), and vowel length differences, and advances in supra segmental characteristics, which included word stress, rhythm, and intonation. Besides, self-confidence, motivation, and independence of the students in practicing pronunciation using AI-supported learning also improved. Conclusion:  AI speech recognition technology is a priceless aid in enhancing the English pronunciation. Feedback that was given to the learners was both regular, individualized, and timely and this resulted to a rise in accuracy and self-regulated learning.  Originality:  The study provides classroom-based evidence concerning the application of AI speech recognition in learning English pronunciation. It shows the possibilities of using AI in teaching pronunciation and increasing the level of learner autonomy and positive results of learning.